A criação de problemas matemáticos na formação inicial do professor que ensina Matemática: a construção coletiva de uma prática de formação - RAIVA, Vladimir Nassone Pedro (Universidade Federal do Pará, 2021)
The research focus on the formation of the mathematics teacher and aims to investigate in which terms the experience in creating mathematics problems, with mathematics teachers-to-be, from their school experience and sociocultural context, focusing their carrier could generate their autonomy, enabling them to become reflexive professionals about their own practice and continuing their professional development. The following question was investigated: from which perspective the initial formal of the mathematics teacher, through mathematics problems creation, focusing his sociocultural context and school experience, can generate a new perspective about the practice and culture of the classroom, about mathematics, through the action reflection and the reflection about the action, enabling professional autonomy? In order to do that, I support the idea that creating mathematics problems, focusing in the sociocultural context and in the teachers-to-be schools experiences, in the action reflection and reflection about the action, having a special look to his carrier (for the action), generate the knowing of the pedagogical action, enables the elaboration of differenced practice, a significative learning and the continuing of his professional development, in an experimental research. Aiming to develop this research, I used, as methodological procedure, an action research or investigative action. The collaborators in this research were 8 mathematics teachers-to-be, in initial formation. The content of the research was mathematics research that were created by the teachers-to-be during the research, discussions and reflections, in pairs and with the class; they received in written form and an initial questionnaire. The questionnaire aimed to know believes of the teachers-to-be to narrow the research about the mathematics concept, mathematics problems, problem solving and experience with mathematics solving problems. Creating problems contributed to the teachers-to-be to be placed as authors of their own learning, authors of their own practice and questioning their believes and conceptions about being a mathematics teacher. Their experiences were brought to the reflections, tried, questioning the pedagogical tradition knowing. In this mathematics problem creation process and reflection, the teachers-to-be understood that the mathematics knowledge construction is a nonlinear process that presents many misunderstandings, due to its coming and going nature. When reflecting about creating their own mathematics problems, it was developed in them the autonomy, because they created the problems and reflected about them. Furthermore, the research enabled the teachers-to-be to become idealizers of practice and not only appliers of recipes outside the school, without the endorsement and reflection from the teacher’s community. This reflection process helped the teachers-to-be to see their own limitations and understand the necessity of reflecting more when demanding tasks from their future students. We constituted a moment to continue their professional development, having in mind that the previous knowledge are necessarily formative. This immersion enabled giving up the docent practices of the teachers-to-be that believed in a noncritical process, because it allowed interpretation, reinterpretation and systematization of past and present experiences. This result made the teachers-to-be look for the pedagogical knowledge about the content, from their limitation of experiences, either previous and the ones acquired during their current formation. They understood that it is possible to see mathematics from a different perspective, the mathematics applications, that are not restrict to numbers; that they can construct their own tasks, mobilizing the previous knowledge to their practice and enable the mathematics content learning.